Curare le psicosi nelle comunità terapeutiche - Introduzione - Dario, Mariopaolo (Il sogno della farfalla, 2018)
The author describes the content of this monographic issue which is entirely dedicated to the management of severe mental illnesses within therapeutic communities. There is first a criticism to the model implemented by Basaglia, according to which the cause of mental illness should be found in social, political and institutional conditioning carried out on patients, which has impaired any further research into the psychopathological and psychodynamic elements behind mental illness and its cure. Then, a new therapeutic model is proposed that is based on Human Birth Theory by Massimo Fagioli and on the education the authors of the articles received at the seminars of Analisi collettiva. Based on the authors’ experiences, the issue’s intent is to put forth a theoretical and methodological approach which, by expounding the specific psychiatric and psychotherapeutic work that is being carried out based on Fagioli’s theory, aims at highlighting the differences with other approaches. The authors are pushed by the ambition of creating and putting forth a specific working model that is based on the new theory on the mind and the unconscious reality. The clinical, therapeutic and educational proposition being put forth in the articles stems from an in-depth activity that has been carried out for many years within a group of study and discussion where psychiatrists, psychologists and operators with different types of expertise have taken part.